Pengaruh Jenis dan Konsentrasi Bahan Pengisi terhadap Karakteristik Komposit Bioplastik Pati Umbi Gadung-Karagenan - Suparwan, Komang Gede Irwan; Hartiati, Amna; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 3 (2021): September, 2021)
This study aims to determine the effect of filler types and concentrations and their interactions on the characteristic bioplastic composites of gadung tuber starch-carrageenan, and to determine the types and concentrations of fillers that produce the best characteristic of the bioplastic composites of gadung tuber starch-carrageenan. This research used factorial randomized block design. The first factor is the type of filler consisting of 4 level that is ZnO, clay, CaCO 3 , nanocellulose. The second factor is the filler concentration consisting of 4 levels 0%, 5%, 10%, 15% (w/w). Each treatment is grouped into two time-based of making bioplastics, so there are 32 experimental units. The data obtained were analyzed of variant and test Tukey’s. Composite gadung tuber starch-carrageenan with nanocelluloce filler get the best a tensile strength value 19,33 MPa, elongation at break 10,47%, modulus young 185,06 MPa, biodegradability for 6 day, and contain asetil (C-O-C), alkenes (CH), alcohol, ethers, carboxylic acids, and esters (CO), alkene (C=C), alkyne (C?C), alcohol (OH). While the composite bioplastic of gadung tuber starch-carrageenan with ZnO filler material with a concentration of 15% the best swelling value 39.32% and the rate of water vapor transmission  0.56 g/hours.m 2 . Keywords :  bioplastic, gadung tuber starch-carrageenan, filler